The impact of green marketing on customer purchase intention: The mediating role of customer concerns and beliefs and green brand knowledge - Mulya, Epifania Adita Wijaya; Kusumawardhani, Amie (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
This study aims to analyse the effect of Green Marketing on Customer purchase intention by using two intervening variables, which are Green Brand Knowledge and Customer concern and beliefs, especially on Unilever customers in Indonesia. In order to analyse the relationship between Green Marketing, customer concern and beliefs, green brand knowledge, and customer purchase intention, a research framework was developed using the Theory of Planned Behaviour. The number of samples used in this study was 192 respondents representing Indonesia. Those respondents came the age of over 17 years old and over, also aware of Unilever as a brand. The Analysis Moment of Structural (AMOS) program was used as a tool for the quantitative and structural analysis of the data utilising the Structural Equation Modelling (SEM) method. The results indicate that Green Marketing positively and significantly affects Green Brand Knowledge and Customer Concern and Beliefs. Also, Green Brand Knowledge and Customer Concern and Beliefs positively and significantly affect Customer Purchase Intention. Moreover, Green Brand Knowledge and Customer Concern and Beliefs have proven to mediate Green Marketing and Customer Purchase Intention. Accordingly, all of the hypotheses in this were accepted.